IMPLEMENTASI AI MENGGUNAKAN CANVA DALAM PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATERI BENTUK-BENTUK ENERGI DI SEKOLAH DASAR - Estuhono Estuhono; Eka Filahanasari; Rika Amrini (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This research is motivated by the low understanding of students towards IPAS subjects, which is caused by the learning media used during the learning process where teachers only use books without using other supporting media and the images in the books are still not varied for students. This affects student learning outcomes. To overcome this, we use learning support media, specifically interactive learning media using the Canva application. This research uses Research and Development (R&D) type with the ADDIE development model which has five stages (Analyze, Design, Development, Implementation, Evaluation). The data collected from the development of interactive media using Canva application is qualitative and quantitative data. Data collection techniques used in this research are interviews, observations, and questionnaires.The validation results of interactive media using Canva are declared very valid. Media validity is assessed by three validators, obtaining a percentage of 95% with a very valid category. Practicality assessed from teacher responses obtains a percentage of 95% categorized as very practical, while practicality results from student responses are 95.38% categorized as very practical. Based on the analysis, it is concluded that interactive media using Canva is very practical. Furthermore, effectiveness assessed from student learning outcomes obtains an average score of 81.43% with a practical category.